TRIM19 enhances the chemosensitivity of endometrial cancer by regulating the TBX2/NRF2 axis - Ning Ding; Yujiao Li; Xiaohui Yu (Discover Oncology)
Abstract Background The chemoresistance occurrence significantly hinders the clinical treatment of advanced cancers, frequently leading to treatment failure. It was already known that tripartite motif protein 19 (TRIM19) enhances the chemosensitivity of human ovarian cancers. However, it remained unknown whether TRIM19 functions in the cisplatin resistance of endometrial cancer. Methods The establishment of cisplatin-resistant Ishikawa cell line (Ishikawa/DDP) was used to investigate the function of TRIM19 in cisplatin resistance. The mRNA levels of specific genes were assessed using real-time quantitative PCR, while protein levels were assessed through western blot analysis. Cell viability was evaluated using the cell counting kit-8. Overexpression of TRIM19 was achieved via TRIM19 plasmid transfection. Furthermore, protein interaction was investigated using an immunoprecipitation assay, and protein stability was evaluated using a cycloheximide chase assay. Results The TRIM19 mRNA levels were dramatically reduced in cisplatin-resistant endometrial cancer tissues. Additionally, the mRNA and protein levels showed significant decreases in cisplatin-resistant Ishikawa cells. Overexpressing TRIM19 greatly enhanced the sensitivity of Ishikawa/DDP and parental cells to cisplatin, while effectively inhibiting T-Box transcription factor 2 (TBX2) protein and ring finger protein 2 (RNF2) signaling. Furthermore, TRIM19 was found to directly interact with TBX2 and facilitate its degradation in Ishikawa/DDP cells. Conclusions TRIM19 effectively decreases TBX2 and NRF2 signaling by interacting with TBX2, consequently reversing the cisplatin-resistance of endometrial cancer.